2002
DOI: 10.1165/ajrcmb.26.5.4737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lung Hyperresponsiveness, Inflammation, and Alveolar Macrophage Mediator Production in Allergy Resistant and Susceptible Rats

Abstract: To better understand asthma pathogenesis, we characterized airway responsiveness, lung inflammation, and mediator production of alveolar macrophages (AM) after allergen sensitization and challenge in two strains of rats showing different susceptibilities in developing airway allergic reactions. Airway responsiveness to acethylcholine was measured 24 h after ovalbumin (OVA) challenge, whereas bronchoalveolar lavages were performed 5 min, 8 h, and 24 h after challenge. Brown Norway rats showed airway hyperrespon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…The transfer of AM from Sprague Dawley rats to AM-depleted Brown Norway rats abrogated both the early phase reaction and airway hyperresponsiveness development, suggesting an important role for these cells in preventing asthma symptoms. We have also demonstrated that OVA sensitization without challenge differentially influences AM cytokine production (TNF, IL-10, IL-12, and IL-13) in Brown Norway and Sprague Dawley rats (8), suggesting that OVA sensitization might differently modulate AM functions in both strains of rats. In the present study, we characterized airway responsiveness and inflammation as well as AM cytokine production and phagocytosis in sensitized and unsensitized Brown Norway rats after OVA challenge.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The transfer of AM from Sprague Dawley rats to AM-depleted Brown Norway rats abrogated both the early phase reaction and airway hyperresponsiveness development, suggesting an important role for these cells in preventing asthma symptoms. We have also demonstrated that OVA sensitization without challenge differentially influences AM cytokine production (TNF, IL-10, IL-12, and IL-13) in Brown Norway and Sprague Dawley rats (8), suggesting that OVA sensitization might differently modulate AM functions in both strains of rats. In the present study, we characterized airway responsiveness and inflammation as well as AM cytokine production and phagocytosis in sensitized and unsensitized Brown Norway rats after OVA challenge.…”
Section: Discussionmentioning
confidence: 70%
“…We have previously demonstrated that Brown Norway rats, a widely used asthma model, develop airway inflammation and hyperresponsiveness after allergen sensitization and challenge in contrast to allergy-resistant Sprague Dawley rats (7,8). The transfer of AM from Sprague Dawley rats to AM-depleted Brown Norway rats abrogated both the early phase reaction and airway hyperresponsiveness development, suggesting an important role for these cells in preventing asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esta resposta via Th2 é 33 mediada pela produção de EROs e citocinas como: IL-4, IL-5 e IL-13. As alterações que caracterizam a asma alérgica são: elevada IgE sérica, intensa secreção de muco, eosinofilia e exacerbada reatividade brônquica (MATTES et al, 2002;HYLKEMA et al, 2002;CAREAU et al, 2002 (ALI et al, 1999;FRANGOGIANNIS et al, 2001;KUBES, 2002 (DAHLEN et al, 1981;FORTES et al, 1991;FARSKY et al, 1995FARSKY et al, , 2004.…”
Section: Hidroquinonaunclassified